Thermodynamic, structural and functional properties of membrane protein inclusion bodies are analogous to purified counterparts: case study from bacteria and humans. Issue 2 (2nd December 2014) - Gupta, Ankit; Iyer, Bharat Ramasubramanian; Chaturvedi, Deepti; Maurya, Svetlana Rajkumar; Mahalakshmi, Radhakrishnan
Abstract : Purification-free transmembrane protein inclusion body preparations for rapid and cost-effective biophysical, functional and structural studies. Abstract : Structural and biophysical characterization of transmembrane proteins that require sufficiently pure protein in high amounts are usually generated in large-scale preparations as inclusion bodies (IBs). However, IB preparations and subsequent purification, is oftentimes laborious, painstaking, time-consuming, expensive and demands protein-dependent customization. We demonstrate that protein purification is dispensable if IBs are sufficiently pure; the latter can be directly used in biophysical and functional experiments. Using an assortment of membrane proteins from bacteria and humans, we validate that IB preparations and their purified counterparts exhibit analogous structure, stability, thermodynamic parameters as well as channel conductance activity. Direct use of crude IBs by circumventing protein purification could find immediate application in speedy generation of high-throughput mutant libraries of transmembrane β-barrels, and possibly helical proteins.